Periphery capitalism — Without question mark - Dieter Senghaas (Intereconomics, 1975)
This article is a rejoinder to Professor Marion Mushkat's contribution “Pheripheric Capitalism?” which was published in INTERECONOMICS, No. 5, May 1975.
Keywords: 330; Development Strategy